Convective Heat and Mass Transfer in Rotating Disk Systems - Shevchuk, Igor V. (Lecture Notes in Applied and Computational Mechanics,, 2009)
The book describes results of investigations of a series of convective heat-and-mass transfer problems in rotating-disk systems, namely, over free rotating disks, under conditions of transient heat transfer, solid-body rotation of fluid, orthogonal flow impingement onto a disk, swirl radial flow between parallel co-rotating disks, in cone-disk systems and for Prandtl and Schmidt numbers larger than one. Methodology used included integral methods, self-similar and approximate analytical solutions, as well as CFD. The book is aimed at the professional audience of academic researchers, industrial R&D engineers, university lecturers and graduate/postgraduate students working in the area of rotating-disk systems.